(untitled) (Medical Forum Monthly, 2024)
Objective: To study the frequency of maternal risk factors in preterm birth. Study Design: Descriptive - Cross sectional study Place and Duration of Study: This study was carried at Hamdard University Hospital, Karachi from January 2013 to December 2013 Materials and Methods: All preterm neonates were examined at Hamdard University Hospital. Mothers who delivered neonates before 37 weeks of gestation and their suspected maternal risk factors contributing to preterm labor were registered on a pre-designed proforma. Keeping prevalence of 14.9%1, bound of error 5%, confidence interval 95%, the calculated sample size is 195. There was Non-probability consecutive sampling. Mothers who delivered live born babies in Hamdard hospital Karachi before 37 weeks of gestation. Babies were born after 37 weeks of gestation and still birth. Results: During the study period, 195 mothers who delivered preterm neonates were included. Out of 195 patients, anemia was found as most common risk factor for preterm delivery in 50.8% mothers, followed by history of previous abortion and premature rupture of membrane with 23.0% and 13.8% respectively. History of previous preterm delivery, pre-eclampsia and antepartum hemorrhage were the least reported risk factors at 4.1% each in our study. Conclusion: Prematurity is still a major problem in Pakistan. Early detection of the most common maternal risk factors as: nutritional status of women (BMI), previous abortions, previous preterm births will reduce the prematurity rate, medical cost and suffering of the parents.